2018
DOI: 10.1111/ppa.12821
|View full text |Cite
|
Sign up to set email alerts
|

Development of three fusarium crown rot causal agents and systemic translocation of deoxynivalenol following stem base infection of soft wheat

Abstract: Fusarium pseudograminearum, F. culmorum and F. graminearum are the most important fusarium crown rot (FCR) causal agents. They have the common ability to biosynthesize deoxynivalenol (DON). To elucidate the behaviour of each of the three species, a comparative study was carried out to investigate symptom progression, fungal systemic growth and translocation of DON following stem base inoculation of soft wheat. FCR symptoms were mainly localized in the inoculated area, which extended up to the second node for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
3
18
1
Order By: Relevance
“…This behavior was also confirmed in a recent study by Beccari et al (2018) where they used the same Fc820 strain on soft wheat. This reveals the opportunity that in barley, in contrast to what occurs in soft wheat, F. culmorum could systemically colonize the head tissues after stem base inoculation.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This behavior was also confirmed in a recent study by Beccari et al (2018) where they used the same Fc820 strain on soft wheat. This reveals the opportunity that in barley, in contrast to what occurs in soft wheat, F. culmorum could systemically colonize the head tissues after stem base inoculation.…”
Section: Discussionsupporting
confidence: 70%
“…These data are related with the quantification of F. culmorum strain Fc820 biomass and also with the work of Covarelli et al (2012) that showed a decreasing concentration of DON from the stem-base to the head of soft wheat. DON translocation from the base to the head was also detected in soft wheat plants inoculated at the stem-base with F. graminearum and F. pseudograminearum (Mudge et al 2006) and it was observed how this characteristic is depending on strain aggressiveness, such as symptoms extension and fungal colonization (Beccari et al 2018). In addition, Mudge et al (2006) demonstrated how strains F. graminearum mutant for tri5 gene (responsible for DON biosynthesis) were unable to colonize the adjacent area of the flag leaf in soft wheat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We optimised a medium for S. indica using commercially available vegetable juice as the main ingredient. Media based on the commercially available vegetable juice V8 have been shown to be useful for growth and sporangia induction of the plant pathogenic fungus Phytophthora [19], and are frequently used for conidia production in different ascomycetes including Fusarium culmorum, Parastagnospora nodorum and Pyrenophora tritici-repentis [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…We optimised a medium for S. indica using commercially available vegetable juice as the main ingredient. Media based on the commercially available vegetable juice V8 have been shown to be useful for growth and sporangia induction of the plant pathogenic fungus Phytophthora [20], and are frequently used for conidia production in different ascomycetes including Fusarium culmorum, Parastagnospora nodorum and Pyrenophora tritici-repentis [24, 25].…”
Section: Discussionmentioning
confidence: 99%